2019
DOI: 10.1152/ajpendo.00359.2018
|View full text |Cite
|
Sign up to set email alerts
|

Hyperandrogenism and insulin resistance induce gravid uterine defects in association with mitochondrial dysfunction and aberrant reactive oxygen species production

Abstract: Women with polycystic ovary syndrome (PCOS) are at increased risk of miscarriage, which often accompanies the hyperandrogenism and insulin resistance seen in these patients. However, neither the combinatorial interaction between these two PCOS-related etiological factors nor the mechanisms of their actions in the uterus during pregnancy are well understood. We hypothesized that hyperandrogensim and insulin resistance exert a causative role in miscarriage by inducing defects in uterine function that are accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
108
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(119 citation statements)
references
References 72 publications
8
108
0
Order By: Relevance
“…13 Gravid uterine defects induced by hyperandrogenism and insulin resistance have been proved to be associated with mitochondrial dysfunction and aberrant ROS production. 16 Since ATP is mainly produced in the mitochondria which are associated with energy metabolism, the loss of ATP content is considered to be a powerful indicator of mitochondrial dysfunction. 38,39 In addition to ATP levels, mtDNA copy numbers and mitochondrial membrane potential can also reflect the integrity of mitochondrial function.…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations
“…13 Gravid uterine defects induced by hyperandrogenism and insulin resistance have been proved to be associated with mitochondrial dysfunction and aberrant ROS production. 16 Since ATP is mainly produced in the mitochondria which are associated with energy metabolism, the loss of ATP content is considered to be a powerful indicator of mitochondrial dysfunction. 38,39 In addition to ATP levels, mtDNA copy numbers and mitochondrial membrane potential can also reflect the integrity of mitochondrial function.…”
Section: F I G U R Ementioning
confidence: 99%
“…[9][10][11] Accumulating evidence have demonstrated that the mitochondrial function and elevated ROS-induced oxidative stress play a key role in the female reproduction and fertility. [12][13][14][15][16] A latest research showed that gravid uterine defects induced by hyperandrogenism and insulin resistance are related to the mitochondrial dysfunction and aberrant ROS production. 16 Moreover, mitochondrial ROS-dependent signaling involves in the regulation of multiple biological processes including cellular proliferation, differentiation as well as physiological, and pathological outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the significant association of PCOS with miscarriage during pregnancy (16, 17), we have recently demonstrated that the effects of HAIR in causing fetal loss is the consequence of uterine and placental defects (18, 19). To this end, we exposed pregnant rats to 5α-dihydrotestosterone (DHT) and insulin (INS) from gestational day (GD) 7.5 to 13.5 and found that this triggered many features of pregnant PCOS patients (including HAIR), as well as increased fetal loss.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, our previous animal experiments have shown that maternal HAIR-induced fetal loss is also associated with the inactivation of antioxidative proteins in the gravid uterus and placenta, namely nuclear factor erythroid 2-related factor 2 (Nrf2) and superoxide dismutase 1 (18, 19), which play an inhibitory role in the ferroptosis pathway (6, 10). Moreover, the expression of several other negative regulators of ferroptosis such as Ho1 (heme oxygenase 1) (6) and Mt1g (metallothionein 1G) (20) are downregulated in the gravid uterus after combined maternal exposure to DHT and INS (18). Increased circulating ROS levels have been observed in both non-pregnant and pregnant rodents in which PCOS features have been induced (19, 21).…”
Section: Introductionmentioning
confidence: 99%